The Affective researcher - Gibson, Andrew G. (Emerald Publishing Limited, 2022)
The wider conditions of society and our own personal circumstances do not simply disappear as we cross the threshold into the research world. The illusion of life in academic research as an abstract 'life of the mind' is unsustainable. Outside academia, wider social changes have come to have an increasingly profound influence on our working lives. Within the academy, changing employment conditions and funding for higher education in recent decades have led to an increasingly insecure existence for those undertaking PhDs and further research. Slow change is happening in response, with more focus being given to precarity within the academy, the mental health needs of early career researchers, and presenting a more honest and open picture of what it's like to build an academic career. The Affective Researcher confronts this challenge of defining a new relationship between researchers and their research. It sets out, simply and accessibly, how you can become a more rounded, authentic researcher. It does this not in terms of the risk management of a methods section, or by cordoning off subjectivity as a threat to supposed objectivity. Nor is it another book on being a more 'effective' researcher. Instead, it sets out a path of how to become a more affective researcher. The chapters draw together a variety of threads from a number of discourses to provide a roadmap, as well as accompanying concepts and tools, for researchers to assert their agency over the research process through the integration of the affective perspective.
Keywords: Research -- Social aspects.; Research -- Methodology.; Education -- Research.; Research methods: general.; elektronické knihy; electronic books